2022
DOI: 10.1007/s10834-022-09873-w
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Like All Those Fees” Pragmatism About Financial Services Among Low-Income Parents

Abstract: Basic financial services facilitate people’s ability to manage their finances, save, and receive payments from employers or the government. Drawing on survey data as well as qualitative interviews with 80 mothers with limited incomes, we find that parents take a pragmatic view and use a wide range of financial services to meet their needs including fintech, prepaid cards, and mobile phone-based solutions, as well as traditional banks. Mistrust in institutions is an important factor in shaping the services moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Financial exclusion has been found to be concentrated among less wealthy, lower income, unemployed or in informal employment, ethnic minorities or immigrants, and those with lower educational attainment level (Ampudia & Ehrmann, 2017;Barcellos & Zamarro, 2021;Bunyan et al, 2016;Coffinet & Jadeau, 2017;Fernández-Olit et al, 2018). Research also points to the mistrust in financial institutions as a potential determinant of not being banked or using certain financial services (Barcellos & Zamarro, 2021;Collins et al, 2023). Yet, bank account ownership rates in Europe and the US have increased to near universal levels largely due to the shift to electronic payment of welfare benefit payments (Ampudia & Ehrmann, 2017;Anderson et al, 2018;Fitzpatrick, 2015), and the introduction of basic and low cost, limited functionality bank accounts (Fitzpatrick, 2015;Washington, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Financial exclusion has been found to be concentrated among less wealthy, lower income, unemployed or in informal employment, ethnic minorities or immigrants, and those with lower educational attainment level (Ampudia & Ehrmann, 2017;Barcellos & Zamarro, 2021;Bunyan et al, 2016;Coffinet & Jadeau, 2017;Fernández-Olit et al, 2018). Research also points to the mistrust in financial institutions as a potential determinant of not being banked or using certain financial services (Barcellos & Zamarro, 2021;Collins et al, 2023). Yet, bank account ownership rates in Europe and the US have increased to near universal levels largely due to the shift to electronic payment of welfare benefit payments (Ampudia & Ehrmann, 2017;Anderson et al, 2018;Fitzpatrick, 2015), and the introduction of basic and low cost, limited functionality bank accounts (Fitzpatrick, 2015;Washington, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…How consumers pay household bills, such as rent, and utility bills, depend on their need for flexibility and transparency. Because low-income households often have limited savings and discretionary income, they value the ability to vary when and how much they pay towards different bills (Collins et al, 2023). For this reason, low-income households are less likely to use automated bill payment methods (Greene & Stavins, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than focusing on accuracy relative to external data, we rely on what people say about their experiences and how their perceptions influence their behavior. Because alternative financial service use is lower among those with the lowest earnings in the U.S., compared to their counterparts with household incomes between $25,000-50,000 ( Friedline & Kepple, 2017; Lawrence & Elliehausen, 2008; Lusardi & de Bassa Scheresberg, 2013) and because previous research with this sample has similarly found limited engagement with alternative financial services in this sample (Collins et al, 2022), we focus on the mainstream credit market. Finally, using a mix of public survey data and interview findings, we show that people have widespread knowledge of the credit data and scoring system.…”
Section: Introductionmentioning
confidence: 99%